Freedom Learning on Early Childhood Education: Implementation of STEAM Method with Loose Parts Media - Rianti, Rianti; Nurjanah, Ika; Latifah, Dewi; Alifah, Nisa; Asyiah, Aas (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aims to describe and analyze the teacher's experience in implementing independent learning using the STEAM (Science, Technology, Engineering, Art and Mathematic) method made from loose parts, namely by creating a fun education so that students can be actively involved in increasing children's creativity, so children's development aspects can develop well.Design/methods/approach – This study uses a qualitative descriptive method. The data analysis technique uses data collection, display, reducing data, and drawing conclusions. We are collecting data using observation, interviews, and documentation. The research subjects were teachers and children of group B of Nurul Iman Kindergarten.Findings – The study findings are in the form of loose parts media used by TK Nurul Iman's teacher in learning with the STEAM method, namely the selection of loose parts material using natural materials such as playing with sand, arranging leaves into necklaces, writing with water on the wall, arranging letters using pieces leaves above the ground. By using loose parts media, aspects of children's development will be achieved, including the artistic aspect: children can make pictures on the sand. Social-Emotional: children have behavior that reflects the attitude of self-confidence, caring, and empathy. Religious and moral values: children can name objects created by God. Language: the child can arrange the pieces of the leaf into a word. Cognitive: children can conceptualize numbers with sand and leaves. Physical motor: children can write using a stick and water on the school wall.Research implications/limitations – The study focuses on implementing independent learning using loose parts media with the STEAM method in students' learning process with natural materials, which have implications for children's development and independent learning.Practical implications – The study can be an additional reference for teachers in developing loose parts of teaching media to implement independent learning.Originality/value – This study provides an in-depth understanding of liberating early childhood by using STEAM loose part media.Paper type: Research paper